Non-Profit Networks - Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2022)
Non-profit organisations and networks are both special. They demand and facilitate trust and can be combined. – – Gemeinnützige Organisationen und Netzwerke sind beide besonders. Sie erfordern und schaffen Vertrauen und lassen sich kombinieren.
Keywords: D02; D85; L14; L31; 650; Network; Non-Profit Organisation; Opportunism; Sharing; Trust